Proximate composition and bioactivities of corn silk (Stigma maydis) for potential cosmoceutical application - Hasanudin, Khairunnisa (2014)
Cosmetics are products that are used to improve the appearance and health of the skin. In order to enhance the appearance and provide a healthy skin, many ingredients that act as antioxidant, whitening and anti-ageing agent are included in the product. However, the source and safety of the ingredients has become the issues among Muslim consumers as there are many products in the market contained dubious ingredients. Some of the products contained lard as substitute oil because it is cheaper and readily available and some of the chemical-based cosmetics products may cause skin problems to the users. As such, the halal and natural-based cosmetic ingredients are an important research area to be studied as it could provide an alternative for consumers especially for Muslims. Therefore, the aims of this study were to determine the proximate composition and to evaluate the antioxidant, whitening, and anti-ageing properties of three types of corn silk which are sweet corn (SC), baby corn (BC) and pearl corn (PC) extracts for potential cosmeceutical application. A study on proximate compositions of SC, BC, and PC powder was conducted and the results showed that BC had the highest moisture (16.5%) and fat content (1.5%), while PC had the highest protein content (20.3%). PC and SC have approximately the same amount of crude fibre which is 21.06 and 21.83%, respectively. However, there is no significant difference was observed among the three samples in ash content. The ash was further analysed for their mineral content which is calcium (Ca), sodium (Na), magnesium (Mg), potassium (K), iron (Fe), and zinc (Zn). The results showed that PC contained the highest amount of Ca (0.17%), K (2%), Fe (0.0097%), and Zn (0.0094%), while SC contained the highest amount of Na (0.026%). Same amount of Mg was observed among SC and PC which is 0.14%. The total phenolic content (TPC) of the extracts are measured using Folin-Ciocalteu reagent and the total flavonoids content (TFC) was determined using aluminium chloride (AlCl3) colorimetric assay. The results of the extracts for TPC and TFC ranged from 6.0 to 20.4 mg GAE/g extract and 1.0 to 58.4 mg RE/g extract, respectively. The antioxidant activity of the samples was then evaluated by using three different assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, metal ion chelating capacity, and β-carotene-linoleate bleaching activity. The SC extract exhibited the strongest activity on all antioxidative assays as compared with BC and PC extracts. The in vitro enzymatic assay was conducted on corn silk extracts to evaluate their whitening and anti-ageing properties. The results showed that all extracts exhibited a low activity for tyrosinase inhibition at all concentrations which ranged from 15.1 to 26.3%. The anti-elastase and anti-matrix metalloproteinase-1 (MMP-1) assay was assessed for anti-ageing properties and the results indicated that SC extract had the highest activity for both assays which is 67.1% and 49.5%, respectively at 20 mg/mL concentration. In conclusions, this study revealed that SC extracts could be a potentially used as alternative ingredient for halal cosmetic products that have antioxidants and anti-ageing properties. Further studies are required to optimize the potential of SC extracts in cosmeceuticals.